Development of size charts of symphysis pubis height measurement for Sri Lankan Population - Dias, T.; Pathmeswaran, A.; Abeykoon, S.; Gunawardena, C.; Pragasan, G.; Padeniya, T. (Wiley-Blackwell, 2015)
INTRODUCTION Fetal growth restriction is responsible for majority of explained and unexplained intrauterine deaths. Screening and diagnosis of fetal growth restriction is one of the main objectives of the antenatal care. Symphysis pubis height measurement (SFH) is routinely measured to assess the fetal growth during antenatal period. Use of SFH charts made elsewhere may either under or overestimate the fetal size in our population. The aim of this study was to construct new size charts for SFH for Sri Lankan population. METHODS This was a prospective, cross-sectional study carried out at the District General Hospital Ampara. In order to increase generalisability 1220 women with normal nutritional and health status and minimal environmental constraints on fetal growth were enrolled during first trimester. Fetal crown–rump length measurement between 11+0 and 13+6 was considered for gestational age assessment in all patients. Each mother considered only once for measurement of SFH for the purpose of this study at gestations between 24 and 41 weeks. SFH was measured using non-elastic, blinded tape using standard technique. For SFH measurement separate regression model was fitted to estimate the mean and standard deviation at each gestational age. Centiles were derived from this mean and standard deviation, assuming that the measurements have a normal distribution at each gestational age. RESULTS A total of 387 mothers had their SFH measured directly. New charts were created for SFH. 10th, 50th and 90th centile values for SFH at 40 weeks are 34, 37 and 41 cm. CONCLUSIONS We have constructed new size chart for SFH. This chart can now be used to assess the fetal size of Sri Lankan population.
E Poster Abstracts (EP5.07) of the RCOG World Congress April 12–15, 2015 Brisbane, Queensland, Australia
Keywords: Pubic Symphysis